Documenting Laboratory Procedures with Video - Wyttenbach, Robert A. (J Undergrad Neurosci Educ, 2015)
Demonstrating laboratory procedures in person during class time can be time-consuming. When procedures are done under a microscope, live demonstration is also impractical because of the limited number of students who can view the demonstration at once. Creating videos beforehand, which students can watch before class and review during lab sessions, solves both of these problems. This article suggests ways to make and distribute high quality video of microscopic procedures.